2010
DOI: 10.1007/s11199-010-9821-3
|View full text |Cite
|
Sign up to set email alerts
|

Fiction, Fashion, and Function: An Introduction to the Special Issue on Gendered Body Image, Part I

Abstract: In this special issue, we showcase innovative research demonstrating the process by which gendered experiences of the body constrain and impact body image. In this first volume, we organized the papers into three research streams that highlight this process. The first stream explores the link between social and/or interpersonal experiences of objectification and body-related selfperceptions and behaviors. The second stream explores different media sources and messages as potent transmitters of gendered body id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Women are exposed to messages of sexualization from two levels: macro (e.g., pornography, mass media, and advertising) and micro (e.g., interpersonal context) (Calogero & Tylka, 2010). Within interpersonal sexual objectification, Fredrickson and Roberts (1997) described two forms: body evaluation (e.g., comments made about the body) and unwanted sexual advances, which are less frequent (Kozee, Tylka, Augustus-Horvarth & Denchik, 2007).…”
Section: Objectification Of Women´s Bodies By Self and Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…Women are exposed to messages of sexualization from two levels: macro (e.g., pornography, mass media, and advertising) and micro (e.g., interpersonal context) (Calogero & Tylka, 2010). Within interpersonal sexual objectification, Fredrickson and Roberts (1997) described two forms: body evaluation (e.g., comments made about the body) and unwanted sexual advances, which are less frequent (Kozee, Tylka, Augustus-Horvarth & Denchik, 2007).…”
Section: Objectification Of Women´s Bodies By Self and Othersmentioning
confidence: 99%
“…Arguably, the deification of the body has characterized Western cultures in the 21 st century, thereby causing the body to become a main element of gender identity. The human form has been subjected to a gendered standard of beauty (for a review see Calogero & Tylka, 2010; Tylka & Calogero, 2010, 2011), and these deep-seated norms have imposed preconceived reference points, leaving little room for other body types (Butler, 1990). As such, human bodies are compared to beauty standards and “are not allowed to naturally develop into a diverse range of shapes, sizes, and attributes” (Calogero & Tylka, 2010, p. 1), instead stigmatizing fat body types (Murray, 2005, 2008; Puhl & Latner, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What is expected and acceptable is often limited to these body ideals, which render people's natural bodies deficient (Calogero and Tylka 2010). Not only are these ideals standardized, they also serve as widely understood models for how women and men should look (Zones 2000), and most destructively, are virtually unattainable without some form of surgical modification (Harrison 2003) or muscleenhancing supplement (Bahrke 2007).…”
Section: Highlights Of Part Ii: Recognizing Individual Differences Inmentioning
confidence: 99%
“…A second aspect of bodily experience, body objectification, refers to viewing one's body as an outside observer rather than as an integral part of oneself (McKinley & Hyde, 1996). A large body of research has documented negative outcomes associated with greater body objectification (Calogero & Tylka, 2010; Frank & Thomas, 2003; McKinley & Hyde, 1996). One existing study on the religion–body objectification relationship (Davis-Quirarte, 2009) found that for women, finding comfort in religion or spirituality was associated with lower self-objectification and body image dissatisfaction.…”
mentioning
confidence: 99%